Anticoagulant Rodenticides Poisonings in Humans and Animals – Short Review - Marcin Zawadzki; Paweł Szpot Szpot (Arab Journal of Forensic Sciences & Forensic Medicine, 2019)
Abstract Anticoagulant rodenticides (AR) are among the most commonly used rodent control pesticides. The current second-generation rodenticides in worldwide use are referred to as superwarfarins. These substances have relatively low toxicity to humans but significant toxicity to animals, including pets. AR work at the level of hepatocytes by blocking the synthesis of plasma coagulation factors II, VII, IX, and X as well as proteins C, S, and Z, resulting in severe coagulation disorders predominant in the clinical picture. Deaths associated with AR poisoning are the result of haemorrhages into the gastrointestinal tract, peritoneal cavity, or intracranial cavities. Medico-legal diagnosis of AR poisonings is based on the clinical picture, autopsy, and histopathological and toxicological examinations.